Two new cryptic species within Periphyllus koelreuteriae (Hemiptera: Aphididae) feeding on Koelreuteria (Sapindaceae) in China - Li, Qiang; Wu, Liying; Cheng, Zhentao; Liu, Zhixiang; Huang, Xiaolei (Zootaxa, 2022)
Based on integrative taxonomic practices by incorporating morphological, genetic, and ecological data, two new aphid species, Periphyllus blackmani Li & Huang sp. nov. and Periphyllus guangxuei Li & Huang sp. nov., are proposed from the known species P. koelreuteriae. Apterous and alate viviparous females of the new species are described and differences with their most similar species P. koelreuteriae are presented. These aphids of P. koelreuteriae species complex feed exclusively on Koelreuteria (Sapindaceae), a native tree group and commonly cultivated as ornamental plants in China. A key to the Chinese species of P. koelreuteriae species complex is provided.